Architecture as an art collection: Palanga case - Nekrošius, Liutauras (Journal of Architecture and Urbanism, 2012)
The trends in Palanga architecture of the second half of the 19th – first half of the 20th century are represented in the National Cultural Heritage List by 10 villas, 14 residential houses, two hotels (Kurhauses of Nemirseta and Palanga), a pharmacy, a spa building, a ship rescue station and a bus station. But such heritage objects reflect the stages in the town development only partially. If the cultural heritage list of Palanga town is treated as a coherent and continuous collection reflecting different stages in architecture and culture of this town (as it should be), it would be relevant to add a few more samples of the mid and second half of the 20th century architecture to the list. Taking into consideration the presence of exclusive Soviet period architectural objects on the list (made according to recommendations of different professional and social communities), and recommendations of the list founders, the following two educational institutions realized less than 50 years ago that these may as well be enrolled as examples of specific historic period and acknowledged artistic style or trend, and as most progressive and/or artistic architectural solutions of the time, to be protected for public information and use purposes: the music school designed by architect I. Likšienė,1981, (Maironio St.8; see Fig. 1) and former Pioneers’ Palace designed by I. Likšienė and G. P. Likša,1985, (now the elementary school, at the address Virbališkės Takas 4; see Fig. 2). These buildings are distinctive examples of contemporary architecture development. At present managed by the local municipality, they are in good physical state, with retained initial qualities of space and volume structure, use of materials, environment and purpose. In the category of accommodation buildings the following may be marked out: the early architectural design works by A. Lėckas, namely, the Žilvinas hotel (Kęstučio St. 34; see Fig. 4, a.), designed and implemented in 1968 as a rest house for 45 guests (21 apartment) on commission of the Council of Ministers of the Soviet Socialist Republic of Lithuania and the Žilvinėlis apartment building for 24 guests implemented in 1970 (Birutės al. 44; see Fig. 4, b.). These objects still owned by the state have been prepared for privatization. Before privatization it is suggested to enroll them on the Cultural Heritage List, identify their valuable qualities, character and level of significance and perform any other required procedures. It is also recommended to make agreements for protection of cultural heritage objects with the new owners of such buildings. The initial protection is also needed for the Rąžė book shop and café building (Vytauto St.84; see Fig. 5) designed by R. V. Kraniauskas in 1967 and considered mature in the artistic sense. The building has retained its small scale, which is characteristic for the resort town, and thus enriches the spatial perspective of the street. Considering its physical shape, functional and aesthetical qualities and the use character, it is also highly recommended to grant the heritage protection status to the administration building Komprojektas (Gintaro St.30,30A; see Fig. 6) designed by G. P. and I. Likša in 1988. The collection of Palanga architecture may also be enriched by the conserved pavilions of the summer reading hall of the National Martynas Mažvydas Library (Vytauto St.72, (1968); see Fig. 7) and Kupeta (S.Daukanto/ S.Dariaus and S.Girėno St., (1969); see Fig. 8) designed by architect A. Čepys; an example of the original concrete plastics, the coffee shop Banga (J. Basanavičius St. 2; see Fig. 10) designed by G. J. Telksnys in 1976–77 and realized in 1979. The present shape and use character of these buildings cause serious threat to their preservation. There is little probability that within the context of the on-going reconstructions traditional acts for enrollment on the heritage list could somehow contribute to the conservation of values of the Vanagupė resort center, the laureate (1984) of prestigious prize by the USSR Council of Ministers (architects A. Lėckas, S. Šarkinas and L. Merkinas; see Fig. 3); the resthouse Guboja implemented only partially in 1976 (in Šventoji, Jūros St 65A., architect. R. Buivydas); resthouse Auska (presently, hotel, Vytauto St.11; architect J. Šipalis, 1977); and the resthouse Šiaulių Tauras (Vytauto St.116, architect G. P. Likša,1983). Nevertheless, the identified architectural, urban, landscape and engineering values of objects and analyzed possible forms for their conservation (ex-situ and in-situ) could become a basis for scientific study of contemporary architecture and urban planning in Palanga resort. Based on their design material, the initial concepts of such objects should be identified and their present as well planned for the future transformations should be analyzed. Such study to be presented publicly (for example, on the National Cultural Heritage List database) could ensure conditions for better understanding of past and present values of the objects, for both, specialists and public at large, and be a highly valuable source of information describing the architecture of the time to be used for information, scientific and professional purposes. Such study may also become a stimulus for preparation of complex regeneration design projects of objects and landscapes, which would comprise the conservation and development needs and add new artistic values. Article in Lithuanian. Architektūra kaip meno kolekcija. Palangos atvejis Santrauka. Dėl pakitusių politinių, ekonominių ir kultūrinių sąlygų XX a. II pusės architektūros ir urbanistikos kūriniai dažnai nebeatitinka šiandienos naudotojų poreikių ir keliamų reikalavimų. Todėl apleidžiami, griaunami ar reikšmingai kinta. Dėl to ryškėja iniciatyvos siūlyti į KVR įtraukti kuo daugiau šio laikmečio kūrinių. Tačiau XX a. IX dešimtmetyje kultūros paminklais tapę naujosios architektūros kūriniai dėl neraiškios saugojimo strategijos, žmogiškųjų ir finansinių išteklių tvarkybai stokos vis tiek nyksta. Todėl kyla abejonių ar registro plėtra bus veiksminga. Straipsnyje Palangos miesto pavyzdžiu nagrinėjamos galimybės sudaryti vėlyvojo modernizmo architektūros kolekciją. Manoma, kad sistemingas kultūriškai vertingų architektūros objektų rinkinys formuojamas apjungiant skirtingus saugojimo metodus gali paskatinti atsakingas institucijas, vietos ir profesines bendruomenes susitelkti atsakingam architektūros paveldo puoselėjimo ir tvaraus naudojimo procesui. Reikšminiai žodžiai: Palanga, architektūros kolekcija, sovietinė modernizmo architektūra, šiuolaikinė Lietuvos architektūra, kultūros paveldo registras, rekreacija, kurortas, turizmas.